Edukasi Etika dan Estetika Berbusana bagi Siswa SMA - Butar-Butar, Khairunnisa; Hasibuan, Elfi Husnita; Dwi Meilasari, Retno Desti; Harahap, Abel Dinda Sartika; Zega, Delfatri Fadya Sara (-, 2026)
The development of teenagers' fashion styles influenced by social media has impacted the decline of awareness regarding clothing ethics and aesthetics within the school environment. This situation emphasizes the need for community service activities in the form of education on clothing ethics and aesthetics for high school students. These activities aim to improve students' understanding and attitudes in applying a manner of dressing that is polite, neat, and aligned with school norms. The community service methods were conducted through interactive lectures, group discussions, mix-and-match demonstrations, clothing selection simulations, and evaluations. The activities took place at SMK Negeri 1 Tanah Tombangan, involving 28 twelfth-grade students. The results showed an increase in students' understanding of clothing ethics and aesthetics concepts, as well as a more positive change in attitudes toward dressing appropriately at school. Practical and contextual education has proven effective in raising student awareness. The results of this activity are important as an effort to develop character and a culture of discipline in the educational environment.